Penerapan Kebijakan Program Pendaftaran Tanah Sistematis Lengkap di Kota Lubuklinggau - Heryani, Vanny; Hartawan, Hartawan (STIE Amkop Makassar, Indonesia, 2025)
This study aims to see the implementation of a complete systematic land registration program carried out at the Lubuklinggau City Land State Office. The focus of this study is based on the theory put forward by Van meter and Van horn (Pramono, 2020: 3), namely: standards and policy targets, resources, communication, disposition and social conditions. This study uses a qualitative method through a descriptive approach with data collection techniques of observation, interviews, and documentation. The types of data sources used in this study are primary and secondary data sources. The results of this study indicate that the implementation of the complete systematic land registration program policy in Lubuklinggau City, especially in Lubuklinggau Utara II District, has been implemented with the largest number in 2023 from other districts, namely 275 certificate issuances. The issuance of certificates for the complete systematic land registration program in Lubuklinggau City has reached 94% with the initial step of conducting socialization to the community.